PERSEPSI GURU TENTANG SISWA ANAK BERKEBUTUHAN KHUSUS (ABK) DI SEKOLAH DASAR INKLUSI JATIMULYA 06 BEKASI - Jelyta Virania; Ainur Rosyid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze teachers’ perceptions of students with special educational needs (SEN) at Jatimulya 06 Inclusive Elementary School, Bekasi. Inclusive education is essential to ensure equal learning opportunities for all children, yet its implementation presents challenges, especially regarding teachers’ readiness in addressing diverse learners. This study employed a quantitative descriptive survey method with a total sampling technique involving 14 teachers. Data were collected through a validated questionnaire and analyzed using descriptive statistics consisting of three indicators: attitude, action, and knowledge. The results show that teachers have generally positive perceptions of SEN students. Teachers demonstrate empathy and acceptance, provide learning support aligned with students’ needs, and understand the characteristics of SEN students, including ADHD, cognitive-affective difficulties, and social-emotional barriers. However, limited training and the absence of special education teachers present challenges. It is concluded that positive teacher perceptions play a crucial role in supporting inclusive learning, although continuous professional development remains necessary